The modeled CA 125 ELIMination rate constant K (KELIM) scores in predicting outcomes in advanced ovarian cancer undergoing neo-adjuvant chemotherapy and interval debulking surgery - Dawadi, Subodh Raj; Shrestha, Binuma; Acharya, Bijaya Chandra; Pandey, Manju; Gurung, Sarita Rana; Subedi, Hem Nath; Chaudhary, Jully; Oli, Asmita; Sharma, Dipti (Nepalese Journal of Cancer, 2026)
Objectives: To evaluate the prognostic utility of standardized KELIM score (derived from CA-125 kinetics) in predicting complete cytoreduction at interval debulking surgery (IDS) following neoadjuvant chemotherapy (NACT) in stage III-IV epithelial ovarian cancer patients at BPKMCH Chitwan.Methodology: Observational study of 46 eligible patients (from 58 total) treated January-December 2025 with carboplatin AUC6 + paclitaxel 175 mg/m² q3w (median 3 cycles). Standardized KELIM calculated using biomarkerkinetics. org calculator (≥1.0 favorable) from serial CA-125 measurements. RECIST 1.1 response assessment, surgical complexity, completeness of cytoreduction (CC0: no gross residual; CC1: